The Effects of Atmospheric Attenuations on C, Ku and Ka Frequency Bands on Satellite Communication System - Udo, E. U.; Nwaorgu, O. A.; Odo, K. O.; Kanu, N. D. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This paper presents the effects of atmospheric attenuations on C, Ku and Ka microwave frequency bands. The atmospheric attenuations such as cloud, rain, oxygen and water vapour have a much significant effect on the transmitting and receiving of signals over satellite communication especially in locations prone to rainfall. This paper analyzed the effects of atmospheric attenuation on satellite communications in selected location in the city of Aba. The rainfall, cloud and gas data were measured and collected from the Nigerian meteorological agency for a period of three months using simulink model to determine the frequency bands within the areas affected by bad weather condition. The method employed the use of Matlab and International telecommunication union radiocommunication sector (ITU-R) prediction model which include the fuzzy logic system to improve the received signal on satellite communication. The results obtained shows that for the exceedance time of 0.01, the attenuation values recorded during the rainfall at elevation angles of 100, 200, 300 and 400 are 14.0440, 17.84080, 25.32430, 13.45070, 17.67230, 24.05440, 14.37360, 18.35890, 26.18720, 13.12440, 16.62090, 23.31440, 12.70280, 16.03920 and 22.36270 while for the exceedance time of 1.00, the attenuation values recorded are 0.639130, 0.88553, 1.41930, 0.605330, 0.834540, 1.32490, 0.62090, 0.91320, 1.48480, 0.585040, 0.804960, 1.26970, 0.560440, 0.767250 and 1.2080 respectively. Therefore, the work reported here showed that the effects of satellite connection which suffers from poor signal quality due to atmospheric disturbances in the study area was minimized.